Special Issue on Northern Ireland “Devolution, Governance and the Peace Process” - Carmichael, Paul; Knox, Colin (Terrorism and Political Violence, 2004)
Devolution and the associated mechanisms of governance - a power-sharing Executive, elected Assembly, cross-border bodies, a reformed system of public administration and civic engagement, are part of the wider mosaic of peace building. Their implementation is an attempt to institutionalise stability and copper-fasten a political settlement. This paper outlines the changing governmental arrangements obtaining within Northern Ireland, as it has shifted tentatively away from Direct Rule. It maps the wider public sector in Northern Ireland, including civil administration (chiefly the Northern Ireland Civil Service), an extended mosaic of non-departmental public bodies (NDPBs) and other public agencies that, together with local government, form a complex multi-layered sub-regional governance. Our contention is that the manner in which the administration of Northern Ireland has been conducted yields fruitful insights into issues of territorial management in other areas afflicted by intractable constitutional wrangles and attendant violence. In short, an agreed system of governance is integral to the transition from conflict to peace (or at least stability) and, in the case of Northern Ireland, was central to the substance of the Belfast Agreement, characterised by a power-sharing Executive
Keywords: Northern Ireland; Governance; public administration